\begin{align}
x_1 -2x_2 + x_3 + 2x_4 \amp =4, \tag{2.1.32}\\
\phantom{2x_1} 3x_2 +x_3 -9x_4 \amp =-1, \tag{2.1.33}\\
\phantom{x_1} x_2 +x_3 -x_4 \amp=-1, \tag{2.1.34}\\
\phantom{3x_1} 2x_2 +5x_3 -x_4 \amp=11, \tag{2.1.35}\\
\phantom{-2x_1} \phantom{+4x_2} -x_3 -3x_4 \amp=1, \tag{2.1.36}
\end{align}
\begin{align}
x_1 -2x_2 + x_3 + 2x_4 \amp =4, \tag{2.1.37}\\
\phantom{x_1} x_2 +x_3 -x_4 \amp=-1, \tag{2.1.38}\\
\phantom{2x_1} 3x_2 +x_3 -9x_4 \amp =-1, \tag{2.1.39}\\
\phantom{3x_1} 2x_2 +5x_3 -x_4 \amp=11, \tag{2.1.40}\\
\phantom{-2x_1} \phantom{+4x_2} -x_3 -3x_4 \amp=1, \tag{2.1.41}
\end{align}
\begin{align}
x_1 -2x_2 + x_3 + 2x_4 \amp =4, \tag{2.1.42}\\
\phantom{x_1} x_2 +x_3 -x_4 \amp=-1, \tag{2.1.43}\\
\phantom{2x_1} \phantom{3x_2} -2x_3 -6x_4 \amp =2, \tag{2.1.44}\\
\phantom{3x_1} \phantom{2x_2} 3x_3 +x_4 \amp=13, \tag{2.1.45}\\
\phantom{-2x_1} \phantom{+4x_2} -x_3 -3x_4 \amp=1, \tag{2.1.46}
\end{align}
\begin{align}
x_1 -2x_2 + x_3 + 2x_4 \amp =4, \tag{2.1.47}\\
\phantom{x_1} x_2 +x_3 -x_4 \amp=-1, \tag{2.1.48}\\
\phantom{2x_1} \phantom{3x_2} x_3 +3x_4 \amp =-1, \tag{2.1.49}\\
\phantom{3x_1} \phantom{2x_2} \phantom{-3x_3} -8x_4 \amp=16, \tag{2.1.50}\\
\phantom{-2x_1} \phantom{+4x_2} \phantom{-x_3} 0 \amp=0, \tag{2.1.51}
\end{align}
\begin{align}
x_1 -2x_2 + x_3 \phantom{+ 2x_4} \amp =8, \tag{2.1.52}\\
\phantom{x_1} x_2 +x_3 \phantom{-x_4} \amp=-3, \tag{2.1.53}\\
\phantom{2x_1} \phantom{3x_2} x_3 \phantom{+3x_4} \amp =5, \tag{2.1.54}\\
\phantom{3x_1} \phantom{2x_2} \phantom{-3x_3} x_4 \amp=-2, \tag{2.1.55}\\
\phantom{-2x_1} \phantom{+4x_2} \phantom{-x_3} 0 \amp=0, \tag{2.1.56}
\end{align}
\begin{align}
x_1 -2x_2 \phantom{+ x_3} \phantom{+ 2x_4} \amp =3, \tag{2.1.57}\\
\phantom{x_1} x_2 \phantom{+x_3} \phantom{-x_4} \amp=-8, \tag{2.1.58}\\
\phantom{2x_1} \phantom{3x_2} x_3 \phantom{+3x_4} \amp =5, \tag{2.1.59}\\
\phantom{3x_1} \phantom{2x_2} \phantom{-3x_3} x_4 \amp=-2, \tag{2.1.60}\\
\phantom{-2x_1} \phantom{+4x_2} \phantom{-x_3} 0 \amp=0, \tag{2.1.61}
\end{align}
\begin{equation*}
\left\{\begin{array}{ccc}
x_1&=&-13,\\
x_2&=&-8,\\
x_3&=&5\\
x_4&=&-2.\end{array}\right.
\end{equation*}